Термодинамический анализ гетерогенных химических реакций в системе "Смесь порошков FE – TI – углеводородная жидкость" под воздействием высоковольтных электрических разрядов - Липян, Евгений Васильевич; Сизоненко, Ольга Николаевна; Торпаков, Андрей Сергеевич; Жданов, Александр Александрович (НТУ "ХПИ", 2015)
Приведен термодинамический анализ химического равновесия для смеси порошков железа и титана в среде углеводородной жидкости под воздействием высоковольтных электрических разрядов. Теоретически обоснована возможность получения карбидов и интерметаллидов из исходной смеси и определены необходимые для этого уровни температуры и давления. Полученные теоретические результаты подтверждены экспериментально при синтезе TiC, Fe₃C и Fe₂Ti.

Thermodynamical analysis of chemical equilibrium for Ferrum and Titanium powders mixture in hydrocarbon liquid medium under the impact of high voltage electric discharges is given. Possibility for obtainment of carbides and intermetallic compounds from components of initial mixture in different phase state is theoretically justified. It is found out that synthesis of Fe₂Ti and TiC is thermodynamically possible at temperatures higher than 300 K and synthesis of Fe₃C and FeTi is possible at temperatures higher than 1100 K. Obtained theoretical results are experimentally confirmed by synthesis of TiC, Fe₃C and Fe₂Ti in Fe – Ti powder mixture after high voltage electric discharge treatment in kerosene.
Thermodynamical analysis of heterogeneous chemical reactions in "Fe – Ti powder mixture – hydrocarbon liquid" system under the impact of high voltage electric discharges
Keywords: энергия Гиббса; парциальное давление; синтез; карбиды металлов; интерметаллиды; Gibbs free energy; partial pressure; hydrocarbon liquid; metal carbides